Population And Diversity Of Phytoplankton On Ramadan In Situ Gintung ‎Lake, South Tangerang, Banten Province, Indonesia - Assuyuti, Yayan Mardiansyah; Rijaluddin, Alfan Farhan; Ramadhan, Firdaus; Tokeshi, Mutsunori (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Changes in the social behavior of Moslems before, during and after Ramadan may impact on lake ecosystems. The aim of this study was to investigate temporal variation in the phytoplankton community of Situ Gintung lake, South Tangerang, Banten Province before, during and after of Ramadan periods 2015. Community composition, abundance, diversity (Shannon-Wiener index H'), dominance (D) and evenness (J) were measured for phytoplankton assemblages. Phytoplankton belonging to 7 divisions and 64 species were found. Phytoplankton belonging to 7 divisions and 64 species were found. The abundance, diversity and evenness indices of phytoplankton showed no significant temporal variation except dominance index..